Market Impacts of Reducing the Prevalence of Bovine Respiratory Disease in United States Beef Cattle Feedlots - Johnson, Kamina Keiko; Pendell, Dustin L. (Frontiers in Veterinary Science, 2017)
Bovine respiratory disease (BRD) is a common endemic disease among North American feedlot cattle. BRD can lead to significant economic losses for individual beef cattle feedlot producers through mortality and morbidity. With promising new management and technology research that could reduce BRD prevalence, this study evaluates the potential impacts of a reduction of BRD in the U.S. beef cattle feedlot sector. Using a multi-market, multi-commodity partial equilibrium economic model of the U.S. agricultural industry, we evaluate the market impacts of reduced BRD to producers from various livestock, meat, and feedstuffs industries. We find that as morbidity and mortality is reduced, beef cattle producers experience losses due to increased supplies (lower beef cattle prices) and increased demand for feedstuff (higher feedstuff prices). Beef cattle processors see gains as the price of beef cattle is lower while feedstuff producers gain from higher feedstuff prices. Producers in the allied industries (pork, lamb, poultry, and eggs) see a small reduction in returns as consumers substitute to less expensive beef products. Consumers see gains in welfare as the increase in beef cattle supply results in lower beef prices. These lower beef prices more than offset the small increases in pork, lamb, poultry and egg prices. Overall, the potential economic welfare change due to management and technologies that reduce BRD is a net gain for the U.S. society as a whole.